Reproduced and emergent genres of communication on the World-Wide Web - Kevin Crowston; Williams, Marie (Information Society, 2000)
The World Wide Web is growing quickly and being applied to many new types of communications. As a basis for studying organizational communications, Yates and Orlikowski (1992; Orlikowski & Yates, 1994) proposed using genres. They defined genres as “typified communicative actions characterized by similar substance and form and taken in response to recurrent situations” (Yates & Orlikowski, 1992, p. 299). They further suggested that communications in a new media would show both reproduction and adaptation of existing communicative genres as well as the emergence of new genres. We studied these phenomena on the World Wide Web by examining 1000 randomly selected Web pages and categorizing the type of genre represented. Although many pages recreated genres familiar from traditional media, we also saw examples of genres being adapted to take advantage of the linking and interactivity of the new medium and novel genres emerging to t the unique communicative needs of the audience.We suggest that Web-site designers consider the genres that are appropriate for their situation and attempt to reproduce or adapt familiar genres.
Proceedings of the Thirtieth Hawaii International Conference on Systems Science (HICSS–30), Maui, HI, USA, January.